Burden of herpes zoster in 16 selected immunocompromised populations in England: a cohort study in the Clinical Practice Research Datalink 2000–2012. Issue 6 (7th June 2018) - Yanni, Emad A.; Ferreira, Germano; Guennec, Morgane; El Hahi, Yassine; El Ghachi, Amale; Haguinet, François; Espie, Emmanuelle; Bianco, Veronique
Abstract : Objectives: Herpes zoster (HZ) is caused by reactivation of varicella-zoster virus which remains latent in individuals after a varicella infection. It is expected that HZ will be more frequent in immunocompromised (IC) individuals than in immunocompetent (IC-free). This study assessed the incidence rate (IR) of HZ in individuals with a wide set of IC conditions and in IC-free individuals. Setting: A retrospective cohort study was conducted in England using data (January 2000 to March 2012) from the Clinical Practice Research Datalink with linkage to the Hospital Episodes Statistics. Participants: A cohort of 621 588 individuals with 16 selected IC conditions and a gender/age-matched cohort of IC-free individuals were identified. The IC conditions included haematopoietic stem cell transplant (HSCT), solid organ transplant, malignancies, autoimmune diseases and users of immunosuppressive medications. Outcomes: IR of HZ per 1000 person-years (PY) was estimated. Proportions of postherpetic neuralgia (PHN) and other HZ complications within 90 days of HZ onset were also estimated among patients with HZ. Risk factors for PHN in IC individuals with HZ were assessed by a multivariate regression model. Results: The overall IR of HZ in the IC cohort was 7.8/1000 PY (95% CI 7.7 to 7.9), increasing with age from 3.5/1000 PY (3.4–3.7) in individuals aged 18–49 years to 12.6/1000 PY (12.2–13.0) in individuals aged ≥80 years. This IR in the IC-free cohort was 6.2/1000 PY (6.1–6.3). The overall IR of HZ varied across IC conditions, ranging from 5.3 (5.1–5.5) in psoriasis to 41.7/1000 PY (35.7–48.4) in HSCT. The proportions of PHN and other HZ complications were 10.7% (10.2–11.1) and 2.9% (2.7–3.2) in the IC cohort, but 9.1% (8.7–9.5) and 2.3% (2.1–2.6) in the IC-free cohort, respectively. Conclusion: IC population contributes to the public health burden of HZ in England. Vaccination might be the most preferable HZ preventive measure for the IC population.